Community Perceptions of Swiftlet Cultivation in Wonomulyo District, Polewali Mandar Regency - Daud Irundu; Rusmidin Rusmidin; Agus Triwandoyo; Zulkahfi Zulkahfi (Jurnal Penelitian Kehutanan BONITA, 2023)
Swiftlet bird (Collocalia fuciphaga) is a non-timber forest product that has high economic value. Swiftlet cultivation is ideally done in the lowlands and away from human settlements. Currently, a lot of swiftlet cultivation has been carried out in residential areas. As is the case in Wonomulyo District, Polewali Mandar Regency, West Sulawesi Province. The existence of this cultivation activity has a lot of impact on the socio-economic community. This study aims to determine public perceptions of swiftlet cultivation activities in Wonomulyo District, Polewali Mandar Regency, West Sulawesi Province. The research was conducted by interviewing 100 respondents who were around the swiftlet cultivation site. Data were analyzed descriptively quantitatively. The results showed an average attitude of 78% in the category of intercepting 75%–100%, which means that people feel very disturbed by Swiftlet bird cultivation.